Dampak Kerjasama Brunei Indonesia Malaysia Filipina East Asean Growth Area (BIMP-EAGA) Terhadap Ekonomi Indonesia - Akhmad Rifky Setya Anugrah; Michael Devone Pangestu (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2023)
Today's global economy is increasingly connected through various forms of economic cooperation between countries. BIMP-EAGA is a regional initiative that aims to promote economic and trade cooperation between the four member countries. This study aims to analyze the impact of BIMP-EAGA (Brunei-Indonesia-Malaysia-Eastern Philippines Economic Growth Area) cooperation on the Indonesian economy. In this study, we use secondary and quantitative data analysis methods to collect information and measure the impact of BIMP-EAGA cooperation on the Indonesian economy. The data used includes statistics on trade, investment, economic growth, job creation, and other related economic sectors. The results of this analysis are expected to provide a better understanding of BIMP-EAGA's contribution to the Indonesian economy. In this study, we will also consider other factors that may affect the results such as national economic policies and external factors. It is hoped that the results of this study can provide insights for the government, policy institutions, and businesses to make better decisions in optimizing the benefits of BIMP-EAGA cooperation. In addition, this research can also serve as a basis for more effective and targeted policy development in utilizing the potential of regional cooperation to boost Indonesia's economic growth.